New classification of donation after circulatory death donors definitions and terminology. (4th May 2016) - Thuong, Marie; Ruiz, Angel; Evrard, Patrick; Kuiper, Michael; Boffa, Catherine; Akhtar, Mohammed Z.; Neuberger, James; Ploeg, Rutger
Summary: In the face of a crisis in organ donation, the transplant community are increasingly utilizing donation after circulatory death (DCD) donors. Over the last 10 years, with the increasing usage of DCD donors, we have seen the introduction in a number of new terms and definitions. We report the results of the 6th International Conference in Organ Donation held in Paris in 2013 and report a consensus agreement of an established expert European Working Group on the definitions and terminology regarding DCD donation, including refinement of the Maastricht definitions. This document forms part of a special series where recommendations are presented for uncontrolled and controlled DCD donation and organ specific guidelines for kidney, pancreas, liver and lung transplantation. An expert panel formed a consensus on definitions and terms aiming to establish consistent usage of terms in DCD donation.